Electrochemical analysis on poly(ethyl methacrylate)-based electrolyte membranes - Mathew, Chithra M. (2015)
Polymer blend composed of poly(vinyl chloride) and poly(ethyl methacrylate) with lithium perchlorate (LiClO4) and the plasticizer ethylene carbonate (EC) mixture with propylene carbonate, γ-butyrolactone (GBL), dibutyl phthalate and diethyl carbonate have been synthesized using the solution casting technique. Structural changes and thermal stability of the films were resolved using X-ray diffraction analysis and thermogravimetric/differential thermal analysis, respectively. The membrane that contains EC+ GBL exhibits maximum ionic conductivity of the order of 1.208 × 10-3 S cm-1 at 303 K. The temperature-dependent ionic conductivity of the polymer membranes has been estimated using AC impedance analysis.